Evaluation of the heterotic potential for seed yield and its attributing traits in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Heterotic potential for seed yield, and yield components in Indian mustard was studied using line × tester analysis involving three lines, and twenty testers for fourteen characters including seed yield, its components, and quality characters. Number of crosses exhibiting significant positive heterosis, heterobeltiosis, and economic heterosis for seed yield per plant were 9, 4 and 3, respectively. Three crosses depicted significant positive heterotic effect for seed yield per plant, viz., GM-2 x PYM-7, GM-3 x PAB-9511 and GM-3 x NUDH-45-1. Among these crosses, GM-2 x PYM-7, and GM-3 x PAB-9511 also exhibited significant and desirable heterotic effect for numbers of siliquae per plant, primary branches per plant and secondary branches per plant. Hence, could be further evaluated in heterosis breeding programme, and simultaneously advanced in segregating generations to obtain desirable segregants for the development of superior genotypes.